PENGELOLAAN LIMBAH DI PT PHAPROS SEMARANG BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG - Andreawan Aditya Wiharmoko, Untung Sri Hardjanto, Retno Saraswati (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
The study is titled: Waste Management in PT. Phapros Semarang, Based on the Act No. 32 of 2009 on the Protection and Environmental Management. The background of this research is PT. Phapros Tbk. Semarang engaged in the pharmaceutical field. Processing of these drugs can result in liquid waste and solid waste that can lead to the surrounding environment and become polluted and unhealthy, then PT. Phapros Tbk. perform first processing of all waste generated. Waste management is carried out by a waste treatment facility located at the Public Services and Household, under the Ministry of Human Resources. Waste resulting from the production process should not be a contaminant to the environment around the plant, especially for the surrounding population. As the formulation of the problem is what are the different types of wastes contained in PT. Phapros Tbk? How sewage PT. Phapros Tbk? What about the implications for waste management violations PT. Phapros Tbk?. The purpose of this study were 1) to determine what types of waste are the results contained in PT.Phapros Tbk, 2) To know how to or waste treatment drugs on PT. Phapros Tbk; 3) To determine whether there are implications of industrial waste PT. Phapros Tbk.